Exploration of Newer/Lesser-Known Oils of Indian Origin: Exploration of Newer/Lesser-Known Oils of Indian Origin - RAM CHANDRA REDDY JALA; SHIVA SHANKER KAKI (Journal of Oilseeds Research, 2023)
CSIR-IICT during 12 th FYP programme investigated on more than 200 treeborne oil seeds. Exploiting Indian Forest base for newer and lesser-known tree-borne oilseed sources for edible and non-edible applications was the objective of this study. Oil seeds namely, Swietenia mahagoni (52% oil content), Calophyllum inophyllum (65%), Melia dubia (43%), Ailanthus excelsa (38%), Mesua ferrea (75%) and Entada Rheedii (12.8%) were some of the oilseeds investigated during the study.